Factors influencing CO2 emissions in China based on grey relational analysis. Issue 4 (16th February 2016) - Huang, Mingqiang; Wang, Bo
ABSTRACT: The increase of greenhouse gas emissions, especially CO2 emissions, have caused the global temperature to rise. As a developing country, China has become the largest CO2 emitter in the world. It is very important and urgent to cut the CO2 emissions down. In this article, the driving forces that influenced China's CO2 emissions from 1995 to 2010 based on grey relational analysis is investigated. It is found that GDP per capita (G), population (P), coal consumption (C), oil consumption (O), natural gas consumption (N), industrial structure (IS), and urbanization (U) play crucial roles in the increase of CO2 emissions, though they have different impacts on CO2 emissions. The sequence of the size of the factors' influence on China's CO2 emissions is C > G > O > N > U > P > IS. Some effective recommendations for improving energy efficiency and reducing the CO2 emissions intensity are proposed.